The educational innovators, 1750-1967 : V.1 : 1750-1880 - Stewart, W. A. C. (William Alexander Campbell), 1915-; McCann, W. P. (Basingstoke, [England] : Macmillan, 2000)
The Eighteenth century. The industrial revolution and after. Continental influences. Some general themes. Epilogue: 1750-1850...
Keywords: Education; Educational change; Educational innovations; Education and state; Educational innovations -- England -- History; Educational change -- England -- History; Education and state -- England